2021
DOI: 10.1051/0004-6361/202039829
|View full text |Cite
|
Sign up to set email alerts
|

Microlensing of the broad emission lines in 27 gravitationally lensed quasars

Abstract: Aims. We aim to study the structure and kinematics of the broad line region (BLR) of a sample of 27 gravitationally lensed quasars with up to five different epochs of observation. This sample is composed of ∼100 spectra from the literature plus 22 unpublished spectra of 11 systems. Methods. We measure the magnitude differences in the broad emission line (BEL) wings and statistically model the distribution of microlensing magnifications to determine a maximum likelihood estimate for the sizes of the C IV, C III… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…However, there are still issues that remain unsolved like the origin of the enhanced asymmetric wings in the broad emission lines of quasar image A (Richards et al 2004;Gómez-Álvarez et al 2006;Lamer et al 2006;Motta et al 2012;Fian et al 2018;Popović 2020;Fian et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still issues that remain unsolved like the origin of the enhanced asymmetric wings in the broad emission lines of quasar image A (Richards et al 2004;Gómez-Álvarez et al 2006;Lamer et al 2006;Motta et al 2012;Fian et al 2018;Popović 2020;Fian et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of extragalactic gravitational microlensing magnification maps (e.g., Wambsganss 2006), which may involve a large number of deflectors and needs to map a huge number of rays, is probably one of the most computationally demanding examples. Gravitational microlensing of extragalactic sources allows one to obtain information on several aspects of lenses and sources that is difficult to obtain by different means (e.g., the abundance and mass of any kind of compact objects in the lens; the quasar structure at several scales, from the large torus (e.g., Popović et al 2020) and the broad-line region (BLR; e.g., Fian et al 2021 and references therein) down to the innermost regions of the accretion disk (e.g., Morgan et al 2010;Jiménez-Vicente et al 2012;Mediavilla et al 2015)). These studies are usually based on the estimate of the statistical likelihood of the observed magnification of the source for different values of the parameters of interest (abundance and mass of the microlenses, size and temperature profile of the source, etc).…”
Section: High-workload Microlensing Magnification Mapsmentioning
confidence: 99%
“…These problems would therefore be difficult to address with preexisting codes without high-performance/ memory hardware and/or too-long execution times. Microlensing and millilensing affect the regions in which AGN and quasars are structured with different strengths depending on their size, from the smallest scales of the event horizon and the innermost stable circular orbit (ISCO; see Mediavilla et al 2015), through the intermediate scales of the accretion disk and BLR (e.g., Morgan et al 2010;Jiménez-Vicente et al 2012;Fian et al 2021), up to the large scale of the torus of scattered light (see Popović et al 2020). For singleepoch microlensing, as the intrinsic brightness of the source is unknown, a baseline defining zero microlensing is needed to measure the impact of microlensing magnification (e.g., Mediavilla et al 2009).…”
Section: Selected Applicationsmentioning
confidence: 99%
“…In addition to constraining the cosmological model, strong lensing time delay systems, typically multiply imaged lensed QSOs, provide valuable insight to astrophysical problems such as constraining distributions of dark and luminous matter of the lenses (Oguri et al 2014;Suyu et al 2014;Sonnenfeld & Cautun 2021;Van de Vyvere et al 2022), and uncovering the properties of distant active galactic nuclei (AGN) and their host galaxies to a level of detail not possible without lens magnification (e.g., McGreer et al 2010;More et al 2015;Fan et al 2019;Yue et al 2022). In the case of the latter, microlensing caused by small structures within the lens have revealed fine-level details of AGN morphology such as accretion disk characteristics (Anguita et al 2008;Motta et al 2012;Braibant et al 2014;Fian et al 2021).…”
Section: Introductionmentioning
confidence: 99%